The Law and Science of Climate Change Attribution - Burger, Michael; Wentz, Jessica; Horton, Radley (Columbia Journal of Environmental Law, 2020)
In recent years, there has been a marked increase in the number of lawsuits seeking to hold governments and private actors accountable for failure to take action on climate change. Climate change attribution science—which examines the causal links between human activities, global climate change, and the impacts of climate change—plays a central role in many of these lawsuits. Attribution science is rapidly evolving, both in regards to attributing impacts and extreme events to climate change and in attributing greenhouse gas emissions to particular actors—and so too is its role in the courtroom and in policymaking. Armed with a growing body of evidence linking increases in atmospheric greenhouse gas concentrations to specific harmful impacts, plaintiffs are pursuing more ambitious claims against governments and emitters for their contribution to, or failure to take action on, climate change. The Law and Science of Climate Change Attribution examines how attribution science is used in litigation and in policymaking, and how litigation and policymaking might influence current and future directions in attribution science. In so doing, the Article indicates where current research factors into various types of climate litigation, and where further work may be most impactful. After a brief Introduction, Part II defines and describes the state of attribution science, articulating core concepts and crafting a vocabulary for law-and-policy audiences to comprehend its methodologies and salience. Part III describes the role that attribution science has played in recent litigation as well as policy-making and planning activities, focusing primarily on examples from the United States but also drawing on international examples. Part IV discusses future directions in the law and science of climate change attribution, addressing questions such as how attribution science can better inform policy-making, planning, and litigation; how parties can best utilize attribution science in climate change litigation; and how courts can respond to the realities and limitations of climate attribution science.